2017
DOI: 10.2147/dddt.s150774
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone mucoadhesive buccal tablets: formulation design, optimization and evaluation

Abstract: The aim of this study was to design and optimize risperidone (RIS) mucoadhesive buccal tablets for systemic delivery as an alternative route. Direct compression method was used for the preparation of buccal tablets, and screening studies were conducted with different polymers to determine their effects on tablet characteristics. Carbopol® (CP) and sodium alginate (SA) were selected as two polymer types for further optimization studies by applying response surface methodology. Tablet hardness (TH), ex vivo resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 39 publications
(42 reference statements)
2
31
0
Order By: Relevance
“…As ALG content in the formulation increased (formulation F3), the significantly (p<0.05) higher mucoadhesive properties were observed. This behavior was in agreement with the results published by Çelik [30], who indicated that the increase in ALG concentration resulted in higher mucoadhesion. The retention time evaluated in ex vivo and in vivo tests was found to be moderately low in film formulation P4, composed of only OLG (Table 4), which might be a result of low molecular weight, low viscosity, and low swelling ability of OLG [17].…”
Section: Mucoadhesive Propertiessupporting
confidence: 93%
“…As ALG content in the formulation increased (formulation F3), the significantly (p<0.05) higher mucoadhesive properties were observed. This behavior was in agreement with the results published by Çelik [30], who indicated that the increase in ALG concentration resulted in higher mucoadhesion. The retention time evaluated in ex vivo and in vivo tests was found to be moderately low in film formulation P4, composed of only OLG (Table 4), which might be a result of low molecular weight, low viscosity, and low swelling ability of OLG [17].…”
Section: Mucoadhesive Propertiessupporting
confidence: 93%
“…The same mucoadhesive drug delivery systems were created for riperidone, another atypical neuroleptic used to treat schizophrenia and bipolar disorder. A mucoadhesive buccal tablet formulation of risperidone allowed 90% release of the drug over 8 h, thereby providing direct systemic delivery of risperidone [ 143 ]. Risperidone-loaded solid lipid nanoparticles drug release and transport studies illustrated the advantages of oral delivery over poorly water-soluble drugs such as risperidone [ 144 , 145 ].…”
Section: Drug Delivery For Schizophrenia and Bipolar Disordersmentioning
confidence: 99%
“…For example, permeation enhancers (e.g., surfactants, bile salts, fatty acids, cyclodextrins, and chelators) have been shown to improve the mucosal permeability and absorption of various compounds (Tsutsumi et al, 1998; Shojaei et al, 1999; Bird et al, 2001; Burgalassi et al, 2006; Sohi et al, 2010; Tian et al, 2012; Prasanth et al, 2014; Patil and Devarajan, 2014; Ojewole et al, 2014; Marxen et al, 2018) by: (i) changing mucus rheology; (ii) increasing the fluidity of the lipid bilayer membrane; (iii) acting on the components at tight junctions; (iv) inhibiting mucosal enzymes; and (v) increasing the thermodynamic activity of drugs (Chinna Reddy and Chaitanya, 2011). In addition, the incorporation of mucoadhesive constituents has been demonstrated to enhance formulation retention time with the sublingual or buccal mucosa (Das and Das, 2004; Razafindratsita et al, 2007; Perioli and Pagano, 2013; Ikram et al, 2015; Yildiz Pekoz et al, 2016; El-Nabarawi et al, 2016; Ammar et al, 2017; Parodi et al, 2017; Celik, 2017; Salehi and Boddohi, 2017; Vasseur et al, 2017; Khan and Boateng, 2018; Razzaq et al, 2018; Sharma et al, 2018). This has been done primarily for solid dosage forms and semi-solid dosage forms.…”
Section: Sublingual and Buccal Formulations Approved And In Clinical mentioning
confidence: 99%
“…It has been evaluated for local drug delivery as a topical anesthetic in Phase I clinical studies. Furthermore, slow-disintegrating and non-disintegrating dosage forms, particularly for buccal drug delivery, have been extensively investigated in the literature to extend or control the release of active substances over a prolonged period (Scholz et al, 2008; Bahri-Najafi et al, 2014; Kaur et al, 2014; Jaipal et al, 2016; Celik, 2017; Lindert and Breitkreutz, 2017; Celik et al, 2017; Farag et al, 2018; Castro et al, 2018b). For example, multilayered films have been developed for controlled drug delivery and are generally designed to remain in their form and slowly release drug over a specified time (Lindert and Breitkreutz, 2017).…”
Section: Sublingual and Buccal Formulations Approved And In Clinical mentioning
confidence: 99%